2020
DOI: 10.1109/jstars.2020.2982714
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Multichannel Volcano-Seismic Classification Using Machine Learning and EMD

Abstract: This article proposes the design of an automatic classifier using the empirical mode decomposition (EMD) along with machine learning techniques for identifying the five most important types of events of the Ubinas volcano, the most active volcano in Peru. The proposed method uses attributes from temporal, spectral and cepstral domains, extracted from the EMD of the signals, as well as a set of pre-processing and instrument correction techniques. Due to the fact that multichannel sensors are currently being ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…RF is parallelizable, performs well for high dimensional signals, quick in prediction/training, robust to outliers and non-linear data, handles unbalanced data and low bias [43]. Lara et al [44] presented a fair comparison of different classifiers (multilayer perceptron neural network (MLP), linear discriminant analysis (LDA), RF, and SVM) for the volcano-seismic signal, where it was shown that SVM outperformed all other classifiers, LDA was the worst performing classifier, and the performance of MLP and RF were approximately the same. Note that RF has lower complexity than MLP.…”
Section: T46mentioning
confidence: 99%
“…RF is parallelizable, performs well for high dimensional signals, quick in prediction/training, robust to outliers and non-linear data, handles unbalanced data and low bias [43]. Lara et al [44] presented a fair comparison of different classifiers (multilayer perceptron neural network (MLP), linear discriminant analysis (LDA), RF, and SVM) for the volcano-seismic signal, where it was shown that SVM outperformed all other classifiers, LDA was the worst performing classifier, and the performance of MLP and RF were approximately the same. Note that RF has lower complexity than MLP.…”
Section: T46mentioning
confidence: 99%
“…A scalable multi-station, multi-channel classifier, using also the empirical mode decomposition (EMD) first proposed by [31] was applied to Ubinas volcano (Peru). The principal component analysis is used to reduce the dimensionality of the feature vector and a supervised classification is carried out using various methods, with SVM obtaining the best performance [116]. Of course, with a multi-station approach particular care has to be taken in order to build a system which is robust with respect to the loss of one or more seismic stations due to volcanic activity or technical failures.…”
Section: Applications To Seismo-volcanic Datamentioning
confidence: 99%
“…The first step of the preprocessing stage is the subtraction of the time-average mean of the signals. After that, the instrumental correction is done by computing the deconvolution associated with the transfer function of the sensor, expressing the seismic signals in their original unity, similarly as in [7]. The goal is to standardize the velocity waveforms obtained by the sensors, originally measured in Seismic Counts, to the unit meter per second (m/s), making the classifier independent on the type of sensor used.…”
Section: A Preprocessingmentioning
confidence: 99%
“…In addition, the work [2] uses attributes in the temporal, spectral, and cepstral domains for the extraction of features, along with the SVM method. In [7], an automatic classification system for volcano events is presented using the empirical mode decomposition (EMD). More recently, the work [8] explored deep learning by using Convolutional Neural Networks (CNNs) to classify spectrograms of seismic events from a South American volcano.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation